Steady-state modeling of reactive distillation columns - doi: 10.4025/actascitechnol.v34i1.9535 (Acta Scientiarum. Technology, 2011)
An algorithm for the solution of the mathematical model featuring reactive distillation process in steady-state columns is analyzed. It has been presumed that each stage´s outlet streams in the model were in phase equilibrium conditions and that chemical kinetics was described by a reaction rate model. Within the context of the developed algorithm a procedure to solve a set of equations in a sequential form and a methodology to produce the initial estimates was defined. Broyden´s method was employed to solve the equations that model the chemical reactions. Algorithm was evaluated by study cases of 2-pentene metathesis and MTBE synthesis. The simulation results were close to results available in the literature and the proposed algorithm proved to be efficient since in both cases the convergence towards a solution was found.